Association between Helicobacter pylori infection and non-alcoholic fatty liver disease for Asian and non-Asian population: A systematic review and meta-analysis - Zhiyuan Ma; Xiajing Chu; Xiajing Chu; Xiajing Chu; Xiajing Chu; Xiang Yan; Wenjin Wang (Frontiers in Public Health, 2022)
BackgroundSeveral studies have revealed a positive correlation between a Helicobacter pylori (HP) infection and the risk of non-alcoholic fatty liver disease (NAFLD). This meta-analysis was conducted to explore further the relationship between HP infection and NAFLD in the Asian and non-Asian populations.MethodsRelevant studies published from inception to July 22, 2021, in the following databases: PubMed, EMBASE, the Cochrane library, and Web of Science were comprehensively searched. The odds ratio (OR) and hazard ratio (HR) with a 95% confidence interval (95%CI) were pooled by the random-effects model or fixed-effects model. Additionally, subgroup and sensitivity analyses were performed. The funnel plot and the Egger test were used to estimate publication bias.ResultsThis meta-analysis included 25 studies involving 107,306 participants. Positive associations between HP infection and NAFLD were found both for the Asian (OR = 1.30, 95% CI: 1.13–1.49, P < 0.01; I2 = 94.30%, P < 0.01) and non-Asian populations (OR = 1.42, 95% CI: 1.04–1.94, P = 0.03; I2 = 44.90%, P = 0.09). Moreover, similar results were observed in the Asian female group (OR = 1.31, 95% CI: 1.17–1.46, P < 0.01; I2 = 46.30%, P = 0.07) but not for the Asian male group. Subgroup analyses for the Asian population showed that there were differences in the association among NAFLD diagnosis methods (P < 0.01) and the study design (P < 0.01). However, subgroup and sensitivity analyses results showed that the association for the non-Asian population was not stable enough.ConclusionsThe data obtained in this systematic review and meta-analysis suggested that an HP infection was associated with an increased risk of NAFLD for Asian and non-Asian populations. However, the association was not found for Asian males. Further studies are required to establish the causal association, especially for the non-Asian population.Systematic review registrationIdentifier: CRD42021266871.